The challenges faced by college students in remote areas in adapting to distance learning during the COVID-19 pandemic: an interpretative phenomenological analysis (IPA) - Hastowohadi Hastowohadi (Indonesian Reseacher for Language Learning and Teaching, 2025)
Learning in Far-flung area is never easy for students to run out their semester-period for over time. Indeed, Covid-19 outbreak limited them to directly learning in face-to-face mode, moreover, the internet access tried to support distance-learning. On the contrary, the students were challenging to link with the internet connection because of the signal, however, they need to struggle out with this unprecedented covid-19 outbreak. Using a qualitative research method, three students who lived in far-flung area were interviewed and the interviews were transcribed verbatim, then analyzed by using Interpretative Phenomenological Analysis (IPA).This study describes the process of the students- struggles, students-adaptation, and the implication for future distance-learning that will be discussed.